Pengaruh Academic Self-Efficacy Terhadap Student Engagement Pada Mahasiswa Fakultas Psikologi Universitas Negeri Makassar - Dian Eka Putri; M. Ahkam Alwi (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
This research aims to determine the influence of academic self-efficacy on student engagement among students at the Faculty of Psychology, Universitas Negeri Makassar. The respondents in this research were 408 active students from the Faculty of Psychology, Universitas Negeri Makassar who were programming or taking lectures offline. The instruments used in this research were the academic self-efficacy scale and the student engagement scale. The data in this study were analyzed using simple regression analysis techniques. The results of data analysis found that there was a positive influence of Academic Self-Efficacy on Student Engagement among Students at the Faculty of Psychology, Universitas Negeri Makassar. This indicates that the higher the academic self-efficacy, the higher the student engagement among students. Conversely, the lower the academic self-efficacy, the lower the student involvement in students. The implication of this research is that it can contribute to the development of knowledge related to academic self-efficacy and student engagement and can be used as a guide in increasing academic self-efficacy and student engagement.